Pembinaan Pupuh Macepat “Surki” pada Sekaa Pasantian Swasti Marga Brata di Desa Selisihan Klungkung - I Kadek Widnyana; Ni Komang Sekar Marhaeni; Ni Putu Hartini (Institut Seni Indonesia Surakarta, 2022)
“Surki” is an acronym for the word sasur siki. Sasur (pasasur) means thirty-five, and asiki means one. Therefore, in this context, pasasur asiki is 36 pupuh (traditional poem) verses/stanzas containing the implementation of 36 items of Pancasila (Five Principles of Indonesia). It is summarized into seven types of pupuh/macapat songs by an art maestro, I Made Sija, namely pupuh Sinom, Pucung, Ginada, Durma, Maskumambang, Pangkur, and Dandang. What makes it unique is that the lyrics contain Pancasila’s noble values, namely divinity, humanity, unity, democracy, and justice, applied in thirty-six pupuh verses that adopt 36 Pancasila values. During Suharto’s New Order in Indonesia, this activity belongs to the Program of Guidelines for the Appreciation and Practice of Pancasila (P4). Then in PKM, the development of the Macapat songs focused on identifying the importance of fostering the Pupuh Macepat “surki” as a medium for guiding Pancasila values for the people of Selisihan Klungkung village. In addition, there has never been a pupuh containing 36 points of Pancasila values and the preservation of the “surki” pupuh by the Pasantian group of people in Selisihan Klungkung village.